Prenatal detection of trisomy 21 and 18 from amniotic fluid by quantitative fluorescent polymerase chain reaction. Issue 2 (February 1998) - Tóth, T; Findlay, I; Papp, C; Tóth-Pál, E; Marton, T; Nagy, B; Quirke, P; Papp, Z
Abstract : Prenatal diagnosis of fetal trisomies is usually performed by cytogenetic analysis on amniotic fluid. This requires lengthy laboratory procedures and high costs, and is unsuitable for large scale screening of pregnant women. An alternative method, which is both rapid and inexpensive and suitable for diagnosing trisomies even from single fetal cells, is the fluorescent polymerase chain reaction using polymorphic small tandem repeats (STRs). In this paper we present the preliminary results of a larger study comparing parallel prenatal diagnoses of trisomies 21 and 18 using cytogenetics with quantitative fluorescent polymerase chain reaction using STR markers. The results obtained by the two techniques were concordant in all cases. This is the first study reporting significant numbers of prenatal diagnoses using the quantitative fluorescent polymerase chain reaction. We believe that further studies on greater numbers of samples will determine the absolute reliability of this technique. These results also provide a model for diagnosis of trisomy from single fetal cells isolated from maternal blood.